Burden of Myasthenia Gravis in the Czech Republic: Analysis of the Nationwide Patient Registry - Voháňka, Stanislav; Tichopád, Aleš; Horáková, Magda; Junkerová, Jana; Jakubíková, Michala; Piťha, Jiří; Týblová, Michaela; Vlažná, Daniela; Breciková, Katarína; Cudny, Jacek; Hájek, Petr (Neurology and therapy, 2025)
INTRODUCTION: The main goal of this study was to describe the Czech population of patients with MG in terms of demographics, disease characteristics, management approaches, and treatment trends. METHODS: We selected all patients, both incident and prevalent, who were enrolled in the Czech MyReg registry between August 24, 2015 and November 19, 2021. For the descriptive analysis, all patients enrolled in the registry, regardless of their date of diagnosis or date of enrolment, were included. We analyzed the following disease-related endpoints: myasthenia gravis composite (MGC) score, forced vital capacity (FVC), and Myasthenia Gravis Foundation of America (MGFA) clinical classification. RESULTS: The incidence showed a consistent increasing trend from 0.62 to 3.13. The mean MGC score was 5.0 (median 4.0, 95% CI 4.7, 5.3) representing mild form of MG. The difference in FVC from the predicted value in patients during and without myasthenic crisis was 58.93% (95% CI 37.27, 80.59) and 75.93% (95% CI 74.87, 77.00), respectively. We identified 70 patients (5.0%) with refractory MG, of whom 58.6% were female. The MGFA classifications in those with refractory vs. non-refractory disease was as follows: IIa 21.8% vs 23.2%, IIb 45.3% vs 33.6%, and IIIb 14.1% vs 4.6%, respectively. CONCLUSION: Our analysis shows that the incidence of MG is increasing in the Czech Republic and that patients with refractory disease, of whom up to 58% are female, have a higher burden of disease than non-refractory patients.
Keywords: Refractory patients; MGQoL15; Myasthenia gravis; MGC score; Burden of disease; FVC